2021
DOI: 10.1002/rmv.2219
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and genotype distribution of human papillomavirus infection in different anatomical sites among men who have sex with men: A systematic review and meta‐analysis

Abstract: Summary Men who have sex with men (MSM) are at increased risk of human papillomavirus (HPV) infection because of their high‐risk sexual behaviours. In this study, a meta‐analytic approach was used to systematically analyse the literature to elucidate the prevalence and genotype distribution of anal, penile, oral and urethral HPV infection among MSM in the world. To carry out this systematic review, five electronic databases including Web of Science, PubMed, Scopus, Embase, and Google Scholar were searched for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 172 publications
(62 reference statements)
1
35
2
Order By: Relevance
“…A systematic review and meta-analysis found that overall prevalence of anal, penile, and oral HPV infection among men who have sex with men were 78.4%, 36.2%, and 15.4%, respectively, with higher rates in HIV-positive than HIV-negative MSM. The most frequent HPV high-risk type detected in the anus, penis, and oral cavity was HPV 16 (19.9%, 4.9% and 3.1%, respectively) 38 .…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review and meta-analysis found that overall prevalence of anal, penile, and oral HPV infection among men who have sex with men were 78.4%, 36.2%, and 15.4%, respectively, with higher rates in HIV-positive than HIV-negative MSM. The most frequent HPV high-risk type detected in the anus, penis, and oral cavity was HPV 16 (19.9%, 4.9% and 3.1%, respectively) 38 .…”
Section: Discussionmentioning
confidence: 99%
“…As demonstrated by the abovementioned study by Beachler et al [24], anal HPV is also more likely to persist compared to the oral infection. The mucosal immune response and the continuous salivary flow in the oral cavity may be responsible for the faster clearance of HPV infection at this anatomic district [5].…”
Section: Discussionmentioning
confidence: 99%
“…The epidemiology of these two infections, separately, has been largely investigated, evidencing the role of sexual exposure in the acquisition and transmission dynamics, particularly in groups with high frequency of sexual contacts, partners, and practices, such as men who have sex with men (MSM) [2,4]. They in fact harbor the highest prevalence of anal and oral infection [3,5]. Unfortunately, little is known about the correlation between these two infections in MSM.…”
Section: Introductionmentioning
confidence: 99%
“…10 An oral HPV infection in the MSM population is generally less frequent than an anal one, however, a large heterogeneity in prevalence data exists among individual studies globally. 11 A recently published meta-analytical study by Farahmand et al estimates an overall prevalence of oral HPV infection of 17.3%, (range from 3.8% to 81.9%), and a prevalence of anal HPV infection of 78.4% (range from 29.3% to 98.9%). 11 Such clear between-study heterogeneity results from both technical factors, such as the method of HPV detection, and sociodemographic factors.…”
Section: Introductionmentioning
confidence: 99%
“…11 Such clear between-study heterogeneity results from both technical factors, such as the method of HPV detection, and sociodemographic factors. 11,12…”
Section: Introductionmentioning
confidence: 99%